All-silicon quantum light source by embedding an atomic emissive center in a nanophotonic cavity - W. Redjem; Y. Zhiyenbayev; W. Qarony; V. Ivanov; C. Papapanos; W. Liu; K. Jhuria; Z. Y. Al Balushi; S. Dhuey; A. Schwartzberg; L. Z. Tan; T. Schenkel; et al. (Nature Communications, 2023)
Abstract Silicon is the most scalable optoelectronic material but has suffered from its inability to generate directly and efficiently classical or quantum light on-chip. Scaling and integration are the most fundamental challenges facing quantum science and technology. We report an all-silicon quantum light source based on a single atomic emissive center embedded in a silicon-based nanophotonic cavity. We observe a more than 30-fold enhancement of luminescence, a near-unity atom-cavity coupling efficiency, and an 8-fold acceleration of the emission from the all-silicon quantum emissive center. Our work opens immediate avenues for large-scale integrated cavity quantum electrodynamics and quantum light-matter interfaces with applications in quantum communication and networking, sensing, imaging, and computing.